EXPLORING BIOMARKERS FOR EARLY DETECTION OF NEURODEGENERATIVE DISORDERS - Khalaf, Tabarak Hadi; Kadhim, Fatima Assad; Faraj, Ali Dakheel; Mansour, Hussein Yahya; Mohammed, Zainab Ali; Sadiq, Zahraa Subhi (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Neurodegenerative disorders, including Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis, present significant challenges due to their progressive nature and the lack of definitive early diagnostic methods. Biomarkers have emerged as essential tools for early detection, enabling timely intervention and personalized treatment strategies. Methods: This review explores recent advancements in biomarker research, emphasizing genetic, proteomic, metabolic, and imaging-based markers. It examines cerebrospinal fluid (CSF) and blood-based biomarkers, such as amyloid-beta, tau proteins, and neurofilament light chain. Additionally, innovative techniques like liquid biopsy and artificial intelligence-driven biomarker discovery are discussed. Results: The study highlights the potential of biomarkers in revolutionizing early diagnosis and patient management. Despite significant progress, challenges remain in biomarker validation, standardization, and clinical translation. The integration of biomarkers into clinical practice can improve diagnostic accuracy and facilitate the development of neuroprotective therapies. Novelty: This review underscores the importance of multi-modal biomarker approaches and the application of machine learning algorithms to enhance diagnostic precision and predictive capabilities. The combination of traditional and emerging biomarker technologies holds promise for transforming neurodegenerative disease diagnostics and treatment strategies.